Temperature dependence of growth and membrane-bound activities of Chloroflexus aurantiacus energy metabolism. - Oelze, J (1983)
The temperature dependence of various activities related to the energy metabolism of isolated membranes and whole cells of the thermophilic bacterium Chloroflexus aurantiacus was determined after phototrophic growth at either 40, 50, or 60 degrees C. The data obtained were expressed by use of Arrhenius plots. Maximum activities were determined at about 65 degrees C for succinate 2,4-dichlorophenol-indophenol reductase as well as NADH oxidase and at about 70 degrees C for Mg-ATPase and for light-induced proton extrusion by cells. Activation energies for Mg-ATPase and light-induced proton extrusion were about 40 kJ mol-1 from 30 degrees C to about 50 degrees C and they increased significantly at higher temperatures. Essentially the same dependency was detectable with NADH oxidase, except for an increase in activation energy below 41 degrees C. All of these responses were independent of growth temperature. Succinate-2,4-dichlorophenol-indophenol reductase showed a change in activation energy around 41 degrees C only with cells grown at 60 degrees C. Differences in the responses of cells grown at different temperatures were identified on the basis of changes from sigmoidal to hyperbolic kinetics for light saturation of proton extrusion. Moreover, the thermostability of proton extrusion was maximal when assayed at the corresponding growth temperatures. In any case, thermostability was lowest at the 65 and 68 degrees C assay temperatures. Differential scanning calorimetry with membranes revealed irreversible heat uptake from about 60 to 72 degrees C. The results are discussed in light of the activation energy for the specific growth rate, which is lowest at temperatures from 40 degrees C to the optimum at 60 degrees C.